2013
DOI: 10.1111/acer.12222
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Type of Alcoholic Beverage Consumed During Adolescence in the Pittsburgh Girls Study

Abstract: Background White, compared to Black, adolescents have higher rates of alcohol use, and show more rapid increases in alcohol use. Racial differences in type of alcohol beverage (i.e., beer, wine, liquor) consumed by youth have received scant attention, and little is known regarding changes in type of alcohol beverage consumed during adolescence, when experimentation may transition to more regular use. Methods This study used repeated measures latent class analysis to identify distinct profiles that represent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
(57 reference statements)
3
7
0
Order By: Relevance
“…We observed for African Americans in our study a significantly lower likelihood of change to either non-heavy or heavy drinking. The finding supports many prior results (Andrade, 2013; Chung et al, 2013; Chung et al, 2014; Lo & Cheng, 2010; Seffrin, 2012; Tucker et al, 2013). When we closely examined RRRs, we observed African American ethnicity to diminish likelihood of change to heavy drinking even more than it diminished change to non-heavy drinking.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We observed for African Americans in our study a significantly lower likelihood of change to either non-heavy or heavy drinking. The finding supports many prior results (Andrade, 2013; Chung et al, 2013; Chung et al, 2014; Lo & Cheng, 2010; Seffrin, 2012; Tucker et al, 2013). When we closely examined RRRs, we observed African American ethnicity to diminish likelihood of change to heavy drinking even more than it diminished change to non-heavy drinking.…”
Section: Discussionsupporting
confidence: 91%
“…This age–drinking-pattern relationship appears stronger in particular subgroups. For example, among White adolescents (White being, until recently, the clear racial/ethnic majority in the United States), increasing age is linked to alcohol consumption at higher levels versus African American adolescents as they age (Andrade, 2013; Chung, Kim, Hipwell, & Stepp, 2013; Chung, Pedersen, Kim, Hipwell, & Stepp, 2014; Seffrin, 2012). Moreover, for White adolescents, drinking is associated with socializing, with sensation seeking, and with peers’ racial self-segregation, while for African American adolescents, it reflects the presence of stress (and efforts to cope with stress) as well as cultural injunction against adolescent drinking (Bradizza, Reifman, & Barnes, 1999; Pedersen, Molina, Belendiuk, & Donovan, 2012; Seffrin, 2012).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…We also found that Black drinkers were more likely to drink hard liquor shots and mixed drinks than beer, malt liquor, or wine; this association may be at least partially driven by momentary perceived discrimination, as the association between race and beverage type was no longer significant when including perceived discrimination in the model. Our EMA findings on beverage type are consistent with prior research using retrospective, global, self‐report measures of drinking behavior (Chung et al., ; Dawson, ; Graves and Kaskutas, ; Siegel et al., ). Importantly, real‐time assessment of beverage type allows for the examination of actual beverage consumed as opposed to what individuals may prefer to drink but seldom drink and allows for momentary factors such as discrimination experiences to be incorporated.…”
Section: Discussionsupporting
confidence: 89%
“…There is also a dearth of research on racial differences in in‐the‐moment drinking characteristics. Some findings suggest that compared to White drinkers, Black drinkers report typically consuming liquor‐containing beverages rather than wine/beer (Chung et al., ; Grant and Dawson, ; Graves and Kaskutas, ; Siegel et al., ) and are more likely to drink in public venues versus at home (Herd and Grube, ; Nyaronga et al., ). However, this research is based on retrospective report.…”
Section: Adhd and Alcohol Use Problemsmentioning
confidence: 99%
“…Consistent with existing literature (Chartier et al, 2009; Chung et al, 2008; Rinehart et al, 2006), increases in endorsement of cognitions and use over time were observed in both racial groups. Also in keeping with prior studies, at most time points, endorsement of cognitions (Antin et al, 2014; Chartier et al, 2009; Randolph et al, 2009; Slutske et al, 2002) and prevalence of alcohol use (Chartier et al, 2009; Chung et al, 2014) were higher in EA than AA girls, with a notable divergence between the two groups around age 14 with respect to positive expectancies and attitude, likely reflecting the emergence of alcohol use in EA girls. This suggests that, in addition to consuming alcohol at an earlier age relative to AA girls, EA girls may also be forming perspectives on alcohol earlier and to a larger extent.…”
Section: Discussionsupporting
confidence: 86%